2017
DOI: 10.3389/fnins.2017.00202
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude Codes for Cross-Modal Working Memory in the Primate Frontal Association Cortex

Abstract: Quantitative features of stimuli may be ordered along a magnitude continuum, or line. Magnitude refers to parameters of different types of stimulus properties. For instance, the frequency of a sound relates to sensory and continuous stimulus properties, whereas the number of items in a set is an abstract and discrete property. In addition, within a stimulus property, magnitudes need to be processed not only in one modality, but across multiple modalities. In the sensory domain, for example, magnitude applies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…In line with results from perception studies of the ANS, neurons in the frontoparietal network were found, specifically in the PFC and IPS, to exhibit numerosity-selective activity during WM (Jacob et al, 2018). Furthermore, supramodal coding of numer-osity memoranda in the frontoparietal cortex has been identified (Nieder, 2017). Interestingly, in contrast to perception, the proportion of numerosity-selective neurons in the PFC and their tuning strength to numerosity have been more prominent than the ones in the PPC during WM retention.…”
Section: Significance Statementsupporting
confidence: 78%
See 1 more Smart Citation
“…In line with results from perception studies of the ANS, neurons in the frontoparietal network were found, specifically in the PFC and IPS, to exhibit numerosity-selective activity during WM (Jacob et al, 2018). Furthermore, supramodal coding of numer-osity memoranda in the frontoparietal cortex has been identified (Nieder, 2017). Interestingly, in contrast to perception, the proportion of numerosity-selective neurons in the PFC and their tuning strength to numerosity have been more prominent than the ones in the PPC during WM retention.…”
Section: Significance Statementsupporting
confidence: 78%
“…Unimodal and multimodal research in both NHPs and humans has identified frequency-specific content in the right LPFC and SMA, thereby suggesting that the WM representations are modality independent in nature (Romo et al, 1999;Hernández et al, 2002Hernández et al, , 2010Barak et al, 2010;Spitzer et al, 2010;Blankenburg, 2011, 2012;Vergara et al, 2016;Schmidt et al, 2017;Wu et al, 2018). However, the explicit relationship between frequency and numerosity still needs to be explored, particularly with respect to the underlying neural codes of numerosity and frequency representations (Nieder, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In our experimental design, target elements were additionally embedded with non-salient items (grey dots) in the relevant hemifield, thus (partly) requiring more effort to perform the task. This might be the reason why the frontal effect was evident also in young participants (note also that single-neuron activity recordings in the primate identified a sustained activity in the prefrontal cortex as one of the physiological correlates of WM, see for example [49]). Moreover, the greater frontal activation observed in the older group is in line with the notion of a posterior to anterior shift in aging (PASA; [50]), with frontal regions compensating for the reduced activation of posterior areas.…”
Section: Resultsmentioning
confidence: 99%
“…As previously mentioned, the PFC is involved in memory, attention, and decision-making (Miller, 2000;Vertes, 2006). In addition, it is considered to act as a hub of cross-modal processing (Fuster et al, 2000;Nieder, 2017). Overall, the PFC follows the developmental milestones described for primary sensory cortices.…”
Section: Development Of the Pfcmentioning
confidence: 97%